Publishing as Method : Ways of Working Together in Asia - Asia Art Archive; Bananafish Books; Grey Projects; Kayfa Ta; Sharjah Art Foundation; Singapore Art Book Fair; Slow Burn Books; Temporary Press; Zine Coop (Seoul; Mediabus, 2023)
Publishing as Method addresses art publishing today, in particular, the practice of small-scale publishing in Asia. As the practice of small-scale publishing has increased among artists, curators, and collectives as a method of mediating their practices in the major cities in Asia over the past couple of years, activities related to producing their output and circulating it have been stimulated. Instead of looking at the culture surrounding small-scale publishing as an individual and independent phenomenon, we attempt to integrate it into its historical and local contexts. To do so, we've invited artists/teams, who practice in China, Hong Kong, South Korea, and the Middle East. They are neither publishing experts in the traditional meaning of the term, nor writers of artist books. Instead, they are graphic designers; artists using web, video, or sound; curators; infoshop, etc.$1 (Bthose who form and connect the conditions of culture as we encounter it today. Their loosely shared attitudes and sensibilities, while not offering a direct answer to the question (3z(BWhat is small-scale publishing?(3y(B, offer an opportunity to approach and utilize publishing as a (3z(Bmethod.(3y (BAlong with the exhibited books, the space named the (3z(BAsia Art Publication Directory(3y (Bintroduces books and documents by about forty publishing initiatives active all over Asia. They are publishing collectives practicing in sixteen cities in Asia, bookshops, art book fairs, archives, artist-run spaces, researchers, and so on. Through their activities, we can imagine the terrain of small-scale publishing in Asia. More detailed information about their practice and their local context is available in the interviews included in the research publication. Publishing as Method features an interview with the founders of Slow Burn Books, Scott Heinrich and Nikki Lam.s
Publishing as Method: Ways of Working Together in Asia is a research project led by South Korean editor, Lim Kyung Yong.
English; Korean
Keywords: N81-390 Study and teaching. Research; Publishing practices; Art Publishing